Compatibility study of bio control agents with agro chemicals: Compatibility study of bio control agents with agro chemicals - U M VYAS,; D S KELAIYA,; R B MADARIYIA, (Journal of Oilseeds Research, 2023)
Agrochemicals were tested for their compatibility with Trichoderma harzianum and Pseudomonas fluorescens under in vitro. Carbendazim @ 50, 100, 250 and 500 ppm, and copper oxychloride @ 1000, 1500, 2000 and 2500 ppm concentrations, completely inhibited growth of T. harzianum. However, chlorpyrifos and cartap hydrochloride @ 250 and 500 ppm were moderately compatible. At initial two lower concentrations, pendimethalin @ 500 and 1000 ppm and fenoxyprop-p-ethyl @ 50 and 100 ppm were compatible with T. harzianum. All the fungicides/combination of fungicides, insecticides and herbicides tested at all their concentrations were completely compatible with Pseudomonas fluorescens isolate-.